Comparison of neointimal coverage between biodegradable-polymer everolimus-eluting stent and durable-polymer everolimus-eluting stent using angioscopy for the patients with acute coronary syndrome. (25th November 2020) - Umemoto, T; Matsuda, J; Hatano, Y; Lee, T; Yonetsu, T; Sasano, T
Abstract: Background: New-generation biodegradable-polymer platinum chromium everolimus-eluting stent (BP-PtCr-EES) is available, which has different polymer and alloy compare to more established stent design, a durable-polymer cobalt-chromium everolimus-eluting stent (DP-CoCr-EES). Purpose: To compare neointimal coverage (NIC) between BP-PtCr-EES and DP-CoCr-EES by using coronary angioscopy (CAS). Methods: A total of 36 patients (44 stents) with BP-PtCr-EES or DP-CoCr-EES who underwent CAS at 1 year after stenting were investigated. We compared angioscopic findings assessed by angioscopy between BP-PtCr-EES (n=18) and DP-CoCr-EES (n=26). NIC grade and yellow plaque grade (YPG) was adopted from earlier reports from grade 0 to 3. We determined maximum (max-) and minimum (min-) NIC grade and heterogeneity score (HGS = max NIC grade minus min NIC grade). We also assessed YPG and the presence of thrombus (TH). Results: Six lesions (33.3%) in BP-PtCr-EES group and 7 (26.9%) lesions in DP-CoCr-EES group were culprit lesions of acute coronary syndrome, which did not statistically differ between the two groups (p=0.74). And there were no significant differences in stent diameter (BP-PtCr-EES: 2.97±0.39 mm vs DP-CoCr-EES: 3.14±0.45 mm, p=0.22) and length (BP-PtCr-EES: 26.9±7.9 mm vs DP-CoCr-EES: 28.4±8.0 mm, p=0.54). In terms of CAS findings, BP-PtCr-EES group has better neointimal coverage than DP-CoCr-EES group (max NIC grade: 2.6±0.7 vs 2.0±0.9, p=0.01. min NIC grade: 1.1±0.8 vs 0.5±0.5, p<0.01), but HGS was almost same (1.6±0.7 vs 1.5±0.9, p=0.70). YPG of BP-PtCr-EES group showed significantly lower than DP-CoCr-EES group (1.0±1.0 vs 1.7±1.0, p=0.02). The rate of TH was significantly lower in BP-PtCr-EES group than DP-CoCr-EES group (25%, n=6, vs 75%, n=18, p=0.03). There were no clinical events such as stent thrombosis or restenosis during the observation period in both stent groups. Conclusion: Superior neointimal coverage and less YPG or TH were observed by CAS in the BP-PtCr-EES group at 1 year after stenting. Clinical significance was still unknown because of no clinical events in both groups. Prospective and large populations studies may be required. Funding Acknowledgement: Type of funding source: None